Dioxo-vanadium(v), oxo-rhenium(v) and dioxo-uranium(vi) complexes with a tridentate Schiff base ligand. Issue 79 (8th August 2016) - Zhang, Yingjie; Fanna, Daniel J.; Shepherd, Nicholas D.; Karatchevtseva, Inna; Lu, Kim; Kong, Linggen; Price, Jason R.
Abstract : The complexation of a tridentate Schiff base ligand with three oxo-metal ions lead to the formations of four new complexes. Abstract : The complexation of a julolidine–quinoline based tridentate ligand with three oxo-metal ions, dioxo-vanadium(v ), oxo-rhenium(v ) and dioxo-uranium(vi ), has been investigated with four new complexes being synthesised and structurally characterised. (VO2 L )·2/3H2 O (1 ) HL (C22 H21 N3 O) = (( E )-9-((quinolin-8-ylimino)methyl)-1, 2, 3, 5, 6, 7-hexahydropyrido[3, 2, 1- ij ]quinolin-8-ol) has a VO2 L neutral mononuclear structure with a five-fold coordinated vanadium metal centre in a distorted trigonal bipyramidal geometry. (ReOL 2 )2 (ReCl6 )·7DMF (2 ) [DMF = dimethylformamide] exhibits a mixed valent rhenium complex with a (ReOL 2 ) + cationic unit in a distorted octahedral metal coordination geometry, charge balanced with (ReCl6 ) 2− anions. [(UO2 )L (H2 O)2 ]2 ·2(NO3 )·HL ·4H2 O (3 ) and [(UO2 )L (CH3 OH)2 ](NO3 )·CH3 OH (4 ) both have (UO2 L ) + cationic mononuclear structures with either coordinated water or methanol molecules in pentagonal bipyramidal coordination geometries for the uranium metal centres. Intra-/intermolecular interactions including hydrogen bonding and π–π interactions are common and have been discussed. In addition, optical absorption and photoluminescence properties have been investigated.